Tradisi dan Reformasi Pesantren: Kurikulum dan Kewibawaan Kyai dalam Pemikiran Zamakhsyari Dhofier dan Nurcholish Madjid - Ali Masdar Fahim; Muhammad Husni (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This paper analyzes the implications of the ideas of Zamaksyari Dhofier and Nurcholish Madjid on reforming pesantren education in Indonesian society. To this end, a critical document analysis is conducted using a qualitative approach, evaluating the ideas presented in Tradisi Pesantren and Bilik-bilik Pesantren, supplemented by secondary literature on pesantren modernization. From the findings, it is apparent that the ideas of the reform-minded thinkers present a comprehensive framework for the five main aspects of pesantren (dormitory, mosque, classical texts, students, and kyai leader); the learning of classical texts through